2007
DOI: 10.1007/s12032-007-9034-y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and management of male breast cancer: a critical review

Abstract: Breast cancer is a rare disease in men representing nearly 1% of the total breast cancer cases worldwide. While treatments developed for women with breast cancer are often applied to treat men with breast cancer, however, lack of awareness of this disease leads to its detection at a later stage in men. This review discusses male breast cancer and draws comparisons with female breast cancer and discusses current treatments available to treat this disease. It is believed that this review shall provide concise an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 44 publications
(47 reference statements)
3
24
0
Order By: Relevance
“…A higher proportion for MBC of 7–14% has been observed in Sub-Saharan countries [32]. Studies from Nigeria depict a proportion of MBC ranging from 3.7% [33] to 8.9% [34] as compared to the US, where the proportion of male breast cancer is 1.12% [35]. Another disconcerting fact was that all the cases of male breast cancer in our study presented in LS, which was an observation similar to studies from Nigeria [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…A higher proportion for MBC of 7–14% has been observed in Sub-Saharan countries [32]. Studies from Nigeria depict a proportion of MBC ranging from 3.7% [33] to 8.9% [34] as compared to the US, where the proportion of male breast cancer is 1.12% [35]. Another disconcerting fact was that all the cases of male breast cancer in our study presented in LS, which was an observation similar to studies from Nigeria [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Data from Central Sudan show that to 2.3% (34/1505) of all breast cancer patients registered at NCI-UG between 1999 and 2010 are males [61], which is over two-fold higher than the proportion reported worldwide [62]. In this regard, the incidence of male breast cancer (MBC) is reportedly higher in sub-Saharan Africa [63].…”
Section: Male Breast Cancer In Sudanmentioning
confidence: 99%
“…This strategy has been studied in females and it has demonstrated that it offers similar survival rates as in the corresponding therapy which was given in the adjuvant setting (Bergh et al,2001). Moreover, aromatase inhibitors and trastuzumab with Her-2/neu have also been subscribed in the preoperative setting in females in phase II randomized studies in combination with chemotherapy (Buzdar et al, 2005;Smith et al, 2005;Pant et al, 2008).…”
Section: Neoadjuvant Systemic Treatmentmentioning
confidence: 99%